2013
DOI: 10.5897/ijnm11.029
|View full text |Cite
|
Sign up to set email alerts
|

Nursing education in Africa: South Africa, Nigeria, and Ethiopia experiences

Abstract: This paper studies the development of nursing education in Africa and it is limited to three countries namely, South Africa, Nigeria and Ethiopia. Two cardinal periods are covered which are, colonial and post colonial. But Ethiopia is the only African country that has technically, never been colonised as it successfully repulsed Italy's attempt at occupying it. The reason for this study is to assist modern states in Africa to learn from the past in order to make good decisions for the present as they build a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…A school of nursing at University College Hospital, Ibadan, was formed in 1952, and in 1954, a Nigerian Midwifery Board was established. 22 In this context, Catholic sisters sensed a serious situation for the future of their hospitals. In 1954 the MMM learned that each region in Nigeria, including the East, where Catholics predominated, was to have only two 'first-class' nurse training schools, one Protestant and one Catholic.…”
Section: Background Of Medical Mission Work In Nigeriamentioning
confidence: 99%
“…A school of nursing at University College Hospital, Ibadan, was formed in 1952, and in 1954, a Nigerian Midwifery Board was established. 22 In this context, Catholic sisters sensed a serious situation for the future of their hospitals. In 1954 the MMM learned that each region in Nigeria, including the East, where Catholics predominated, was to have only two 'first-class' nurse training schools, one Protestant and one Catholic.…”
Section: Background Of Medical Mission Work In Nigeriamentioning
confidence: 99%
“…This could be attributed to the few PhD faculty members in the department and the country in general. Moreover, in Nigeria, there are twenty-seven post basic nursing education programs including mental health-psychiatry, midwifery, and peri-operative nursing, education program among others [4]. Furthermore, there is no in-country nursing journal.…”
Section: Challenges For the Reformsmentioning
confidence: 99%
“…It costs D160, 000 (Dalasi; D1 = $43) for two years of fulltime course work including Master's thesis on a research project [11]. Studies have shown that the South African Nursing Council, Nursing and Midwifery Council of Nigeria and the Ethiopian Nursing Association have identified certain strategies to overcome such problem through collaboration with and financial support from organizations such as WHO, Canadian Nurses Association, Royal College of Nursing, United States Agency for International Development, UNICEF and World Trade Organization for funds for those willing to pursue higher degrees in nursing education [4].…”
Section: Challenges For the Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“… All: World Bank (WB) (), World Health Organization (WHO) (); Ethiopia: Ali (), Ethiopian Food, Medicine and Health Care Administration and Control Authority (); India: Indian Nursing Council (), Malik (); Hong Kong: Nursing Council of Hong Kong (n.d.), Nursing Council of Hong Kong Professional Development Committee (); South Africa: Dolamo & Olubiyi (); Uganda: Mbalinda et al. (), Uganda Nurse and Midwife Council (n.d.); United Kingdom: Royal College of Nursing (), Nursing and Midwifery Council (); United States: Woolf & Aron (), National Council of State Boards of Nursing, Inc. (NCSBN) (); Vietnam: Flemming (), Health Partnership Group (), Ministry of Health (); Zambia: General Nursing Council of Zambia (GNC) (n.d.), Libetwe & Mweemba (). …”
Section: Introductionmentioning
confidence: 99%